MX100, a new Escherichia coli tester strain for use in genotoxicity studies - Kranendonk, M (1996)
The development of a new Escherichia coli tester strain for use in metabolic and mechanistic studies of genotoxins, strain MR2101/pKR11, has recently been reported. This strain, a derivative of the E.coli K12 laboratory strain AB1157, has sensitivity towards the detection of base-substitution mutagenesis, monitored by the reversion of arginine auxotrophy [argE3, (ochre)]. Besides arginine, MR2101/pKR11 is auxotrophic for histidine (hisG4), leucine (leuB6), proline (ΔproA) and threonine (thr-1). MX100 was developed to overcome the auxotrophy for four amino acids of MR2101/pKR11 which are non-essential for the mutagenic responsiveness of the strain. We restored the biosynthesis for these four amino acids in MR2101/pKR11, resulting in strain MX100. This strain showed an almost 2-fold increase in mutagenic activity relative to MR2101/pKR11 with a set of diagnostic mutagens (aflatoxin B1, benzo[α]pyrene, 4-nitroquinoline-1-oxide, 2,7-dimethyl-benz[a]anthracene and others) and was further characterized with other types of mutagens in which it showed sensitivity towards the detection of oxidative (H2O2, t-butyl-hydroperoxide, cumene-hydroperoxide, KO2) and carbonyl mutagens (methylglyoxal, malondialdehyde). As MX100 seems to have the right characteristics of a versatile genotoxicity tester strain and due to the extensive genetic and physiological knowledge of E.coli K12 in general and AB1157 in particular, we propose that MX100 could serve as mother strain for the development of specialized tester strains, of interest in studies of metabolism and/or mechanism of action of genotoxic carcinogens.